Syringic Acid in Canarium odontophyllum for Diabetes and Obesity – A Review - Gilbert Ringgit; Cheong, Bo Eng; Muhammad Dawood Shah; Noor Atiqah Aizan Abdul Kadir; Shafiquzzaman Siddiquee (Springer Nature, 2025)
Syringic acid (SA) is a phenolic compound with a significant role in the treatment of diabetes and obesity. Syringic acid possesses anti-obesity and anti-diabetic properties; however, the potential of syringic acid derived from the native Bornean fruit Canarium odontophyllum (C. odontophyllum) for managing diabetes and obesity remains undocumented. This brief discussion explores the possible mechanisms associated with syringic acid’s structure and its potential therapeutic effects in managing diabetes and obesity. The relevant information is gathered from previous reports on syringic acid, related to molecular docking studies involving syringic acid-associated enzymes and protein residues. The potential mechanism of syringic acid derived from C. odontophyllum with chemical structure characterized by a benzene ring with hydrogen bonds and its high affinity for enzymes and protein residues targeting diabetes and obesity, including hexokinase 2 (HK2), glycogen synthase kinase (GSK), 2BEL, protein kinase D (PKD), insulin receptor substrate-1 (IRS-1), and insulin receptor beta (IR-β). This review paper provides alternative insights into syringic acid derived from the seasonal fruit of native Bornean fruit associated with molecular docking, structural advantages and mechanism of action in diabetes treatment.